Formulation of a nanoemulsion for topical delivery of raloxifene - Hasan Ali, Ebrahim Mohammed; Sengupta, Pinaki (2017)
Objective: Raloxifene, a selective estrogen receptor modulator is used in the treatment of osteoporosis and invasive breast carcinoma in postmenopausal women. The effectiveness of oral therapy of raloxifene is not satisfactory because of its low water solubility, higher first pass metabolism and poor bioavailability (2%). The main objective of this research was to develop a topical aqueous based nanoemulsion formulation of raloxifene to improve the bioavailability of this lipophilic molecule. Methodology: The appropriate type and quantity of oil, surfactant and cosurfactant was selected and determined after different screening studies. Oil phase was selected based on the solubility of raloxifene in different oils and oil-surfactant-cosurfactant mixture. For a selection of surfactant, 15% V/V surfactant solution in water was prepared and the oil phase was gradually added into it with vortexing until the sample started to become milky. Cosurfactant was selected based on the capability of different surfactant-cosurfactant mixtures in enhancing the amount of water incorporated into the formulation. The nanoemusion of raloxifene was prepared by dissolving raloxifene in the oil phase and gradually adding to the emulsifier solution with vortexing. Results: A mixture of sunflower oil: tween 20: transcutol in a ratio of 1.0:0.5:0.5 showed the maximum solubility for raloxifene. Tween 20 as a surfactant showed the maximum emulsification capability. Addition of transcutol as cosurfactant allowed more water to be incorporated into the formulation. The 3:1 ratio of tween 20: transcutol (S/CoS) and 1:7 ratio of sunflower oil: S/CoS showed the highest stability of the nanoemulsion formulation. Conclusions: A new nanoemulsion formulation has been developed for topical delivery of raloxifene. Hypothetically, presence of surfactant and nano sized oil droplets will improve the skin permeability and therefore, enhance the bioavailability of raloxifene.